Jewish aspects in avant-garde : between rebellion and revelation - Gelber, Mark H., 1951-; Sjöberg, Sami (Perspectives on Jewish texts and contexts ;, 2017)
"This volume will deal with the significance of the avant-garde(s) for modern Jewish culture and the impact of the Jewish tradition on the artistic production of the avant-garde, be they reinterpretations of literary, artistic, philosophical or theological texts/traditions, or novel theoretical openings linked to elements from Judaism or Jewish culture, thought, or history."--Provided by publisher